Orff instruments as an incentive and tool in the creative space of children’s musical development in early and preschool education - Zubčić, Ana; Katavić, Marijana; Košta, Tomislav; Habuš Rončević, Snježana (Rethinking childhood II: child and space, 2026)
Music education in preschool institutions is an integral part of the unified educational process and work with children, contributing to the holistic development of the child, particularly their creative potential, relationship with the environment, social interaction, creative abilities, reading skills, imagination, and aesthetic sensitivity to music. Early childhood and the preschool period are crucial for the development of all children’s abilities. Through listening to and creating music, the child engages all senses and develops a natural need to express their musical experience in a comprehensive manner. In an effort to stimulate the child’s creative and musical potential, various modalities such as body percussion, rhythmic and melodic percussion instruments, as well as children’s or Orff instruments, are introduced and utilised. This study aims to investigate whether preschool educators in Zadar implement activities based on Orff instruments and to what extent they perceive themselves as competent in conducting such activities. One of the research objectives is to examine whether preschools are equipped with Orff instruments, which should be considered a key prerequisite for the implementation of music activities. The research was conducted among educators from the municipal kindergartens Radost and Sunce in Zadar. Additionally, the study describes an activity based on the Carl Orff music-pedagogical concept, which involved children from a mixed-age group (3–5 years) in the Voštarnica kindergarten in Zadar over a period of two months.